1996
DOI: 10.1177/00957984960223008
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Ethnic Identity Development in African American Youth: The Role of Rites of Passage

Abstract: Contemporary adolescent rites-of-passage interventions within the African American community are designed to positively influence the ethnic identity of African American youth through activities that provide historical and cultural information, teach intellectual and social skills, and promote values that are consistent with African American culture and community needs. Unfortunately, it is unclear how consistent these interventions are with current developmental research and theory. This article presents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Programs such as ''Rites of Passage'' and mentoring programs that exist within the AfricanAmerican community can be beneficial in helping at-risk youth overcome potential barriers to successful achievement (Brookins, 1996). Social workers should encourage utilization of existing programs by assisting youth and their families to develop an action plan that links the external and internal resources.…”
Section: Strategy 5: Seek Culturally Appropriate and Successful Intermentioning
confidence: 99%
“…Programs such as ''Rites of Passage'' and mentoring programs that exist within the AfricanAmerican community can be beneficial in helping at-risk youth overcome potential barriers to successful achievement (Brookins, 1996). Social workers should encourage utilization of existing programs by assisting youth and their families to develop an action plan that links the external and internal resources.…”
Section: Strategy 5: Seek Culturally Appropriate and Successful Intermentioning
confidence: 99%
“…10,20,23 Although the process by which youth identify role models is not well understood, efforts to enhance ethnic identity by providing positive images and examples of individuals ethnically matched to the target population, in the context of service provision, would also seem to be indicated. For providers serving increasingly diverse and at-risk youth populations, ethnic identity may be more malleable and amenable to intervention than the structural inequalities that contribute to adverse outcomes.…”
Section: Does Having a Role Model Help One Group More Than Others?mentioning
confidence: 99%
“…More recent qualitative data drawn from African American and Latino high school and professional samples confirm the importance of this aspect of parental influence. 18,19 Encompassing a complementary and supportive theme in the literature, 10,[20][21][22][23] role model selection also reflects critical elements of psychosocial functioning and selfperception, particularly ethnic identity. Using qualitative methods, Taylor 24 found that identification of a role model distinguished high school from college samples of lowincome African American males.…”
mentioning
confidence: 99%
“…At the community level, there is growing evidence that African American boys and girls who participate in formal passage rituals may experience less role discouragement, identity confusion, and distress in the transition to adulthood (Boyd-Franklin & Franklin, 2000;Brookins, 2005;Williams, 2004). Rites-of-passage rituals were imperative in many traditional African societies and are increasingly practiced within African American communities today.…”
Section: Protective Emic Cultural Strengthsmentioning
confidence: 99%